Identity and image of a university : case studies of management and students at Luleå University of Technology - Siegbahn, Caroline; Öman, Jenny (2004)
Universities, as all other organizations in today’s Sweden, are challenged with their survival in the face of increased competition and decreasing student enrollment. Universities have been forced to turn their attention towards identity and image in order to differentiate themselves from competition. The purpose of this thesis is to gain a deeper understanding of identity and image of a university. To reach our purpose we have explored, described and started to explain the identity and image of a university as viewed by the university’s management and students. Two case studies, one based on management’s perspective and one based on students’ perspective, have been conducted on Luleå University of Technology. Our study shows that that: both tangible and intangible factors comprise the identity of a university and in order to differentiate, these factors must include more unique features than those traditionally suggested by theory. Moreover, a range of factors and characteristics comprises a university’s image, and in order to generate a positive image it is essential for the university to retain their credibility. Furthermore, our study proves that all parts of the identity management process are necessary in order to create a strong image. Our study also reveals that one of the most important aspects of this process is communication since clear communication allows the university to convey the same identity to all stakeholder groups. Finally our investigation shows that image and reputation are effects of the identity management process, whereas competitive advantage not necessarily is an outcome. Validerat; 20101217 (root)